Drones - Applications in Agriculture - Debangshi, Udit (Chronicle of Bioresource Management, 2021)
Agriculture sector is now facing several challenges, among which, the scarcity of labour, increasing cost of production, environmental degradation etc., are very important. Furthermore, India’s population is expected to reach 1.64 billion by 2050 and it is required to produce up to 333 million tonnes of food grains in near future. In this context, information and communication technologies (ICT) driven tools and solutions can help people to make better decisions. Among many emerging technologies which can provide solutions, unmanned aerial vehicles (UAVs), often known as drones is one of the most recent innovation. It is also a non-human centric, transparent, evidence-based technology. It can save labour while also achieving social distancing norms during COVID 19 and national lockdown. In this article, an effort was made to synthesize available information on multiple uses of drones in Agriculture.